2019
DOI: 10.3390/ijms20194940
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Role of MicroRNAs in Breast Cancer

Abstract: MicroRNAs (miRNAs) are small non-coding RNA molecules which function as critical post-transcriptional gene regulators of various biological functions. Generally, miRNAs negatively regulate gene expression by binding to their selective messenger RNAs (mRNAs), thereby leading to either mRNA degradation or translational repression, depending on the degree of complementarity with target mRNA sequences. Aberrant expression of these miRNAs has been linked etiologically with various human diseases including breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
200
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(203 citation statements)
references
References 165 publications
(193 reference statements)
3
200
0
Order By: Relevance
“…Cancer cells manipulate the balance of microRNAs to favor cell growth and survival, proactively adapting their expression profile to the evolving state of cancer progression [17]. Over 900 microRNAs have been characterized, and their role within breast cancer and treatment failure is reviewed elsewhere [16,18].…”
Section: Introduction-history Of Breast Cancer Current Management Amentioning
confidence: 99%
“…Cancer cells manipulate the balance of microRNAs to favor cell growth and survival, proactively adapting their expression profile to the evolving state of cancer progression [17]. Over 900 microRNAs have been characterized, and their role within breast cancer and treatment failure is reviewed elsewhere [16,18].…”
Section: Introduction-history Of Breast Cancer Current Management Amentioning
confidence: 99%
“…MiRNAs are non-coding RNA molecules, which play important roles in physiological and pathological processes by post-transcriptional regulation of gene expression [12]. In recent years, numerous studies revealed the function of miRNAs as potential biomarkers and key modulators in breast cancer [13,14]. CSCs are at least in part responsible for chemoresistance in tumors [4,15], the chemotherapeutic-dependent regulation of miRNAs in BCSCs are yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miRNAs involved in the regulation of the Wnt/β-catenin signaling pathway play a crucial role in modulating EMT and tumor metastasis [115]. miR-374a is highly expressed in metastatic breast cancer and it downregulates epithelial markers, such as E-cadherin, and upregulates mesenchymal markers, such as N-cadherin and vimentin, thus promoting EMT.…”
Section: Mirna In Metastasismentioning
confidence: 99%